ANALISIS RASIO PERMODALAN BMT AL IQ-TISHODY MATARAM - Aryani, Menik (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2020)
This study is entitled "Capital Analysis Ratio of BMT Al Iq-Tishody Mataram" The purpose of this study is to determine the level of sharia health and compliance in the AL-Iqtishody Mataram BMT 2019 on aspects of capital based on cooperative classification standards according to the cooperative ministerial decree and small business and intermediate number 07 / Per / Dep.6 / IV / 2016. Analyze cooperative financial statements based on the Decree of the Minister of Cooperatives and Small and Medium Enterprises Number 07 / Per / Dep.6 / IV / 2016, Evaluate the financial performance of cooperatives. This study uses 1 type of assessment of health aspects and components in the form of: Capital. The assessment will find out how healthy Al Iq-tishody BMT is in terms of finance, and how obedient in predetermined sharia principles. From these calculations the BMT Al Iq-tishody was classified as "Fairly Healthy" Cooperative. This is because it has an unfavorable value because BMT AL-Iqtishody does not yet have a sharia supervisory board, does not yet have equity participation and financing originating from Islamic financial institutions and also cooperative management does not yet have an educational certificate for management of Islamic financial institutions issued by competent parties.Â Keywords: Capital, Sharia Health and Sharia compliance